The optimization of on-board H2 generator control strategy and fuel consumption of an engine under the NEDC condition with start-stop system and H2 start. (9th November 2016) - Ji, Changwei; Yu, Menghui; Wang, Shuofeng; Zhang, Bo; Cong, Xiaoyu; Feng, Yu; Lin, Shen
Abstract: The addition of hydrogen has been proven to be an effective way for improving the engine efficiency and lowering carbon-related emissions. However, difficulties in the hydrogen onboard storage and production are barriers for its practical applications in the automobiles. This paper first conducted a series of experiments to optimize the control strategy of the on-board hydrogen generator and then proposed a start-stop system and pure hydrogen start strategy for the engine to improve overall fuel economy. Bench tests for optimizing the control strategy of on-board hydrogen generator was conducted on a four-cylinder gasoline engine equipped with an electronically controlled hydrogen port-injection system at engine speeds of 1000, 1500, 2000 and 2600 rpm, respectively. For a given engine speed, the intake manifolds absolute pressure (MAP) was increased from 25 to 100 kPa. The test results showed that the production of hydrogen could be started when the engine speed was greater than 1300 rpm and MAP was higher than 48 kPa to gain better fuel economy. A simulation model was built based on AVL CRUISE code to investigate the overall fuel consumption of vehicle equipped with on-board hydrogen generator and adopted the start-stop system-and-hydrogen start strategy under the New European Driving Cycle (NEDC). The numerical results demonstrated that the adoption of start-stop system could reduce the fuel consumption by 5.09% when the hydrogen generator was continuously worked within the whole NEDC. By further adopting the optimal working range acquired from this test, the vehicle fuel consumption could be reduced by 8.43%. Highlights: A smart idle elimination and pure hydrogen start strategy is proposed. An optimum operating range of hydrogen generator is found. A numerical model is adopted to simulate the vehicle performance. Fuel consumption is further decreased in the optimized range.